Checklist of floral species at the Institute of Forestry, Pokhara Campus, Pokhara, Nepal - Miya, Mahamad Sayab; Gautam, Deepak (FORESTRY: Journal of Institute of Forestry, Nepal, 2021)
Plants are a component of biodiversity and support life system on earth. Exploration of plant species is important to aquire knowledge on plant biodiversity and their distribution. This study documents floral species in the Institute of Forestry, Pokhara Campus, Nepal. The Campus is one of the academic institutions for producing forestry graduates. The plant species were listed from 2020 to the first half of the year 2021 by walking along the accessible routes inside the Campus. A total of 331 species of plants from 276 genera and 99 families were recorded. Fabaceae family represented the maximum number of plant species (n=26) followed by Asteraceae (n=25) and Poaceae (n=21). 43% of the total species recorded were herbs. 31% of the total species were trees. 16 species were invasive alien plant species (IAPS) and four species are listed under Appendix-II of CITES.